Design and implementation of an automatic solar tracking system for a monocrystalline silicon material panel using MPPT algorithm. (2021) - Rajesh, T.; Tamilselvan, K.S.; Vijayalakshmi, A.; Narendra Kumar, Ch.; Anitha Reddy, K.
Abstract: The energy crisis is the biggest problem in the world today. Renewable energy resources are gaining worldwide priorities to reduce reliance on traditional resources. Solar energy is gaining prompt attention as significant means of increasing uses of renewable energy. Owing to variability in the day night cycle and also owing to seasonal changes, the variability in solar energy occurs daily. World population is increasing quite rapidly. Non-renewable energy sources such as oil and coal have been extinguishing for the past decade, making it a severe problem to supply the planet with sustainable electricity. Yet, solar power plays an important primary energy role. This paper introduces a dual axis solar tracking device from which maximum solar energy can be collected by implementing the work by coding a suitable Maximum Power Point Tracking (MPPT) algorithm for a Monocrystalline solar panel. This work is carried out using microcontroller, Light Dependent Resistor (LDR), dc motor, and Arduino.